The effect of sevoflurane on the spatial recall ability and expression of apolipoprotein E and Î² amyloid in the hippocampus in rats - Jiang, Wanwei; Wang, Qinghui; Yajing Liao, Yajing Liao; Sun, Yue; Yang, Rui (Cellular and Molecular Biology, 2020)
This study aimed to observe the recent spatial recall ability and the changes of expression of hippocampal apolipoprotein E (ApoE) and amyloid Î² protein (AÎ²) in adult rats after inhaling sevoflurane anesthetic drugs, and to analyze the mechanism of action. For this purpose, a total of 54 adult SD clean-grade rats were selected in this study and were randomly divided into the sevoflurane anesthesia group, carrier gas group and control group, 18 rats in each group. The rats in the carrier gas group were inhaled with 1 L/min of oxygen O2+1 L/min air mixed carrier gas for 2 h, and the rats in the sevoflurane anesthesia group were given 3.2%sevoflurane for 2 hours based on the carrier gas group, the control rats were naturally reared. Before the model was copied, the Morris water maze experiment was performed before the material was taken. Some rat brain tissues were extracted on the first day (T1), the third day (T3), and the seventh day (T7) after model replication. The immunohistochemistry was used to measure the mean optical density (MOD) value of APOE and AÎ² in hippocampal CA1, CA3 and DG regions. The indicators above at different time points of each group were compared and analyzed. Results showed that the number of crossing the original platform at each time point, the residence time of the original platform quadrant, the number of entering the original platform quadrant, and the percentage of the original platform quadrant residence time in the sevoflurane anesthesia group and the carrier gas group were compared, and there were no significant differences between two groups (P>0.05). Compared with the carrier gas group, the MOD values of APOE in the hippocampus at T1 and T3 time points in the sevoflurane anesthesia group were decreased (P<0.05), the MOD values of AÎ² in the hippocampus at the T7 time point were increased (P<0.05). It concluded that Inhalation of 3.2%sevoflurane has no obvious damage to the recent spatial recall ability of adult rats. Within 7 days after inhalation of 3.2% sevoflurane, it can inhibit hippocampus AÎ² deposition through down-regulating APOE expression level. The critical time point for hippocampal AÎ² increasing was 7 days after anesthesia.